Study on Finite Element Model of the Prefabricated Reinforced Concrete Beam-Column Joints with Grouted Sleeves - Xiaoyong Luo; Hao Long; Ya Ou; Shuang Dong (Advances in Civil Engineering)
Based on the monotonic tensile test of grouted sleeve specimens conducted, this paper uses multifactor regression analysis to construct the equivalent constitutive relationship of grouted sleeve specimens under uniaxial tension. The study based on this constitutive relationship of grouted sleeves and the effect of bond and slip between steel and concrete were considered. The prefabricated reinforced concreted beam-column joints with grouted sleeves were presented with finite element software ABAQUS. The seismic behavior of prefabricated reinforced concreted beam-column joints with grouted sleeves under low-frequency cyclic loading was then investigated. In addition, parametric studies via finite element analysis were performed to examine the influence of various parameters on the strength and energy dissipation capacity of the specimens. The simulation results show that plastic deformation was mainly observed near the beam-column interface; the hysteretic curve of this joint was plump. The test results showed that good energy dissipation and displacement ductility capacities can be achieved. The error of yield load between the numerical simulated and experimental result was 7.11%, the error of peak load was 6.88%, the error of ultimate load was 3.76%, and the error of displacement ductility was 7.84%. Results showed that the calculated results obtained in the paper agree well with test results from the references. The finite element model adopted in this paper can reflect the seismic behavior of the prefabricated reinforced concrete beam-column joints with grouted sleeves by using equivalent constitutive relation.